2020
DOI: 10.3390/genes11091006
|View full text |Cite
|
Sign up to set email alerts
|

Rimbp, a New Marker for the Nervous System of the Tunicate Ciona robusta

Abstract: Establishment of presynaptic mechanisms by proteins that regulate neurotransmitter release in the presynaptic active zone is considered a fundamental step in animal evolution. Rab3 interacting molecule-binding proteins (Rimbps) are crucial components of the presynaptic active zone and key players in calcium homeostasis. Although Rimbp involvement in these dynamics has been described in distantly related models such as fly and human, the role of this family in most invertebrates remains obscure. To fill this ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…These unique and simple characteristics of Ciona enable us to study their neural activity during embryonic development at a single-cell level. For instance, in peripheral nervous systems, recent research has found that two isoforms of the RIM-binding proteins (Rimbps) family, one of the crucial components of the presynaptic active zone and Ca 2+ homeostasis in flies and humans, were also expressed in Ciona (Coppola et al, 2020).…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…These unique and simple characteristics of Ciona enable us to study their neural activity during embryonic development at a single-cell level. For instance, in peripheral nervous systems, recent research has found that two isoforms of the RIM-binding proteins (Rimbps) family, one of the crucial components of the presynaptic active zone and Ca 2+ homeostasis in flies and humans, were also expressed in Ciona (Coppola et al, 2020).…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…This volume is clearly not intended to be an exhaustive collection of studies on invertebrate animals, but we hope that the collection of articles presented here will give a general idea of both the type of studies carried out with invertebrate metazoans and the diversity of animal models used. Thus, we can read works carried out with Acropora corals [ 1 ], with several mollusc species such as the cephalopod Nautilus pompilius [ 2 ], the gastropod Crepidula fornicata [ 3 ] or the bivalve Mytilus galloprovincialis [ 4 ], as well as a study with the planarian Schmidtea mediterranea [ 5 ], or with several chordates such as two cephalochordate species ( Branchiostoma lanceolatum [ 6 ] and Branchiostoma floridae [ 7 ]) and two urochordate species ( Ciona robusta [ 8 ] and Phallusia mammillata [ 4 ]).…”
mentioning
confidence: 99%
“…Two other articles in this volume are focused on two biological processes of great importance, the mechanisms at work in synapses and the meiotic division, using different species of tunicate as models. In the first one, Coppola and collaborators [ 8 ] studied the expression of the Rab3 interacting molecule-binding protein ( Rimbp ) gene and its expression regulation through the identification of the genetic regulatory elements present in its genomic locus. This work highlights different expression domains for each Rimbp isoform in the nervous system of C. robusta larvae and will certainly help to understand the function of this family of genes in the context of ascidian embryogenesis.…”
mentioning
confidence: 99%